A gênese dos eventos tornádicos no corredor sul-americano - Iensse, Amanda Comassetto (2018)
South America since its discovery is the scene of great fights, Portugal and Spain were constantly fighting for this portion of land. But not only are there fights on earth as well as in the atmosphere, as the constant arrival of air masses and the formation of disturbed currents in this region made it the tornado corridor of South America. In order to contribute to the studies of tornados, if you understand the genesis of these events in the South American corridor. To meet the objectives, a database was constructed from the confirmed records and in Excel the municipality and the date of occurrence were identified. The atmospheric systems were identified by synoptic charts and spatial with the aid of ArcGIS 10.22. Subsequently, the records were spatialized as to their hypsometry and climate. Finally, a comparison was made between 3 maps (tornado density map, tornado threat map and population density map). The results showed that there was a growth of the records from the 1990s, especially in the year of 2006, where South America was under the influence of La Niña weak. It was found that the atmospheric system with the highest participation of record, was the FPA due to its ability to provide pressure gradients facilitating the formation of severe weather. The climate-type map was also constructed in ArcGIS 10.5 with Köppen cartographic base (1931), and showed that 77% of events occurred in the Cfa climate type. Finally, when buying the maps of population density, density of tornados and density of threat, it is concluded that most of the registers are where there is bigger population, corroborating the map of MCCARTHY; SCHAEFER (2004), except in the interior of Brazil. It was concluded that the results of this research, sought to assist in the understanding of tornado records in the South American Corridor. However, although it is a complex subject to work on, it is a fertile area for searching for the number of records in recent years and the increasing dissemination of the possibility of occurrence by the media.